Conflict appearances in the work of William Shakespeare - Dilnozaxon Murotova Abʹsa·lom's daughter (Zien Journals, 2022)
This article analyzes the conflicts in Shakespeare's works. Examples of the writer's work have been illustrated and detailed about the use of conflicts in literature
Keywords: dramatics; comedy; collation conflict; literature